Pengaruh E-Service Quality Dan Customer Relationship Management Terhadap Kepuasan Pelanggan Pengguna Aplikasi Dana - Mahendri, Wisnu; Sholiha, Mas Azzaqiatus (JURNAL ADMINISTRASI KANTOR; Vol 10 No 2 (2022): Jurnal Administrasi Kantor (Desember 2022)DO - 10.51211/jak.v10i2.1988, 2023)
Technological developments have made people's lifestyles increasingly changing to become completely online with the emergence of the internet as a link. Competition is getting tougher, making companies have to pay more attention to e-service quality and the relationship between companies and customers so that customers still feel satisfied and loyal. The DANA company is trying to build a quality e-service that meets the needs of consumers. This study aims to analyze the effect of electronic e-service quality and Customer Relationship Management on customer satisfaction among DANA users in Jombang. The data analysis technique in this study used multiple linear regression analysis. Data collection by distributing questionnaires online to DANA users. The results of this study indicate that the e-service quality and CRM provided by the DANA company have made customers feel satisfied when using it. The relationship between the company and the customer is also the value of customer trust when making transactions.   Keywords : CRM, Customer Satisfaction, DANA, E-Service Quality,